Implementation of the Shiddiqiyah Order in the Community in Sumber Sirih Village, Waru District - Hanifatus Sholehah; S. Fathiyatul Jannah; Faridatul Jannah (Maklumat: Journal of Da'wah and Islamic Studies, 2024)
This article discusses the implementation of the Shiddiqiyah order in the Sumber Sirih village community, Waru sub-district, where in this research used description-based qualitative research methods, researchers went directly to the field to look for data and interviews with the Sumber Sirih village community, in the implementation of this order the Kiai used three events. which aims to get closer to God, the three ways are increasing feelings of gratitude, getting closer to God by holding routine activities once a week on Sunday. Friday and the last thing is to build brotherhood among Muslims. This aims to get closer to Allah SWT.